2008
DOI: 10.4321/s1137-66272008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de la varicela y el herpes zóster antes de la introducción de la vacunación sistemática infantil en Navarra, 2005-2006

Abstract: Varicella is an acute and highly contagious disease produced by the varicella-zoster virus, which leaves lasting immunity. Herpes zoster is produced by reactivation of a latent infection of the same virus. The introduction of systematic and free vaccination against varicella in children of 15 months in Navarre from 2007 onwards can be expected to produce important epidemiological changes. For this reason we describe the previous epidemiological situation in the period from 2005 to 2006. We analysed all cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
3
9
0
4
Order By: Relevance
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 87%
“…19 In Navarre, which has an excellent public health system, the proportion of patients seen by private family physicians and dermatologists is very low.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Según los datos de incidencia disponibles en algunas Comunidades Autó-nomas y los resultados de las encuestas seroepidemiológicas, la infección por el virus de la varicela sería de adquisición precoz afectando predominantemente a los niños de edad preescolar y escolar [37][38][39][40][41][42] .…”
Section: Carga De La Enfermedadunclassified
“…La carga de la enfermedad es semejante en todos los países desarrollados [4][5][6][7]38,133,137,138 .…”
Section: Carga De La Enfermedadunclassified